Caracterização do uso e cobertura do solo nos agroecossistemas familiares da terra indígena tikuna Santo Antônio, município de Benjamin Constant/AM - Dantas, Luana da Silva (Brasil, 2021)
In most Brazilian biomes, the land use system exerts great pressure on vegetation cover, especially forest cover. This pressure varies in intensity depending on the location, the type of use, the structure and size of the areas used. Anthropogenic activities have been increasing degradation due to changes in land cover and land use. To do so, characterize the components of land use and land cover in agroecosystems using satellite images for manual classification of satellite images from GoogleTM Earth Pro with on-site visits to assess the classifications. From this, the use and land cover in the agroecosystems in the study area were characterized by remote sensing to proceed with the description of the land use and land cover categories based on the techniques used. In order to fulfill the objectives of analyzing the dynamics of use of scrub in farmland environments in the agroecosystems of the Tukuna Santo Antônio Indigenous Land, in the municipality of Benjamin Constant/AM. As a result, 13 categories of use were described, containing the image of the place - sample (Google Earth), the Typology - Class, and the criteria for visual interpretation. Maps were generated for each class of land cover and land use with a mosaic of satellite images from July/2017 that provided information on the dynamics, giving clues in time and space, of land use and occupation and farmers' activities. Thus, we observe the change in vegetation in the mapped polygons and the representation of land cover and land use classes. When analyzing the results, it can be observed that the highlighted class was the forest (forest) 56%, in second capoeira old (13%), followed by capoeira in regeneration (12%) and new (10%). Exposed soil (3%), felled forest (2%), burned forest (2%) and farmland (2%) are areas affected by the deforestation of forest cover, however together they add up to less than 10% of the total area of Santo Antônio Indigenous Land.